Pengaruh Pengendalian Internal, Whistleblowing System, dan Kompetensi Pegawai Terhadap Pencegahan Fraud dengan Moralitas Individu Sebagai Variabel Moderasi - Marini, Rici; Muhsin,; Helisa Noviarty, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of internal control, whistleblowing system, and employee competence on fraud prevention efforts, and evaluate the role of individual morality as a moderating variable. The background of this study is based on the high number of fraud cases in the public sector, which indicates that the supervisory system and individual ethics are not optimal. The research was conducted at the Financial and Development Supervisory Agency (BPKP) of West Kalimantan Province using an explanatory quantitative approach. Primary data was collected through distributing questionnaires to 36 purposively selected respondents. Data analysis was conducted by utilizing WarpPLS 8.0 software to test the direct relationship between variables as well as the moderating effect of individual morality. The results of the analysis show that internal control and whistleblowing system have a positive and significant effect on fraud prevention. In contrast, employee competence does not show a significant effect. In addition, individual morality is proven to strengthen the effect of internal control on fraud prevention, but does not strengthen the effect of the whistleblowing system or employee competence. These findings emphasize that the effectiveness of the supervisory system needs to be supported by individual moral integrity to optimally prevent fraud. This research is expected to make an empirical contribution in strengthening the supervisory system in the public sector and in shaping a clean organizational culture and integrity.